2024
DOI: 10.15421/192401
|View full text |Cite
|
Sign up to set email alerts
|

Preference Digital Wallet by Generation Z with the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) Model Approach and Perceived Risk

Rani Elasaria,
Nurabiah

Abstract: Purpose: This empirical study explores the use of digital wallets by Gen Z in Indonesia. This study uses a quantitative approach and collects data through distributing questionnaires to respondents online. The instrument in the questionnaire includes questions related to the effect of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, and perceived risk on behavioral intention, habit and behavioral intention on use behavior, and perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Additionally, consistent results were noted in the studies by Yang et al (2015) on mobile payment intention, Damghanian et al (2016) on online banking, and Almousa (2011) on online shopping intentions, all reporting significant negative impacts. Conversely, Piarna et al (2020) and Elasaria (2024) found that performance risk could positively influence intentions, mediated by perceived risk. In contrast, Zhu et al (2022) reported no significant relationship among Thai consumers.…”
Section: Resultsmentioning
confidence: 94%
“…Additionally, consistent results were noted in the studies by Yang et al (2015) on mobile payment intention, Damghanian et al (2016) on online banking, and Almousa (2011) on online shopping intentions, all reporting significant negative impacts. Conversely, Piarna et al (2020) and Elasaria (2024) found that performance risk could positively influence intentions, mediated by perceived risk. In contrast, Zhu et al (2022) reported no significant relationship among Thai consumers.…”
Section: Resultsmentioning
confidence: 94%